2008
DOI: 10.1016/j.ejca.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk factors for relapse of melanoma

Abstract: AimTo identify lifestyle factors affecting risk of relapse.MethodsA comparison of 131 relapsed melanoma patients with 147 non-relapsers.ResultsRelapsers were more likely to report financial hardship using a number of different measures including access to holidays and feeling financially insecure (odds ratio (OR) 5.7, 95% confidence interval (CI) (1.5, 21.4)). Relapsers worked longer hours (mean 37 h per week compared with 31, p = 0.02). There was no reported difference in stress associated with recent life ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
(35 reference statements)
1
15
0
3
Order By: Relevance
“…To categorize SES, this study used the ACORN ® system, which has been used in a number of epidemiological studies . This system has advantages in that economic data are drawn from a wide range of sources in addition to property values.…”
Section: Discussionmentioning
confidence: 99%
“…To categorize SES, this study used the ACORN ® system, which has been used in a number of epidemiological studies . This system has advantages in that economic data are drawn from a wide range of sources in addition to property values.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment of patients took place between May 2000 and January 2005 from geographically-defined areas of the UK (the Northern and Yorkshire, Oxford, Trent and West Midlands Health Regions). This study is described fully elsewhere in a paper in which questionnaire data collected from 274 of the 300 cases were reported (41). …”
Section: Methodsmentioning
confidence: 99%
“…Low socioeconomic status is also regarded as a poor predictor of melanoma outcomes and has been associated with disparities in utilization of sentinel lymph node biopsy (Zell et al, 2008;Bilimoria et al, 2009). Financial concerns were found to influence outcomes of disease in melanoma patients; a retrospective study found that perceived financial difficulty (compared to patients with an equivalent deprivation score) was related to recurrence risk, after adjusting for histological characteristics of the melanoma (Beswick et al, 2008). Examination of SEER data of melanoma patients for the effect of marital status on melanoma stage, after controlling for a number of factors including histology, anatomic site, and socioeconomic status, suggested that unmarried patients had a higher risk of late-stage cutaneous melanoma diagnosis (McLaughlin et al, 2010).…”
Section: Social Historymentioning
confidence: 99%